2021
DOI: 10.1101/2021.01.04.425241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Batf-mediated Epigenetic Control of Effector CD8+ T Cell Differentiation

Abstract: SUMMARYThe response of cytotoxic T cells to their cognate antigen involves rapid and broad changes in gene expression that are coupled with extensive chromatin remodeling. Here, we study the mechanisms by which the basic leucine zipper ATF-like transcription factor Batf helps regulate this process. Through genome-scale profiling, we observe critical roles for Batf in inducing transcriptional changes in stimulated naive cells, while affecting the chromatin at several levels, namely binding of key transcription … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 116 publications
1
3
0
Order By: Relevance
“…In addition, the well-known function of BATF in T H 17 and CD8 + T cells is the recruitment of IRF4 to the AP-1–IRF composite element sites. Our data confirmed that whereas BATF and IRF4 cooperate, the gene expression of BATF was broadly up-regulated in tumor-infiltrating T reg cells compared with that of IRF4, suggesting more comprehensive roles of BATF in T reg cells, as reported in effector CD8 + T cells ( 46 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, the well-known function of BATF in T H 17 and CD8 + T cells is the recruitment of IRF4 to the AP-1–IRF composite element sites. Our data confirmed that whereas BATF and IRF4 cooperate, the gene expression of BATF was broadly up-regulated in tumor-infiltrating T reg cells compared with that of IRF4, suggesting more comprehensive roles of BATF in T reg cells, as reported in effector CD8 + T cells ( 46 ).…”
Section: Discussionsupporting
confidence: 82%
“…Given that BATF and IRF4 work together ( 45 , 46 ), the relationship between BATF and IRF4 binding regions was examined. In cluster 5, almost all IRF4 peaks overlapped with the BATF ChIP-seq peaks, suggesting that BATF and IRF4 may work together in certain differentiations of tumor-infiltrating T reg cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Tsao et al evaluated the transcriptome and epigenome of differentiating CD8 + T cells in mice, highlighting the central role of BATF. Through genome-scale profiling, they observed that BATF induces transcriptional changes in stimulated naïve cells and establishes the effector cell transcriptional and epigenetic program through the cooperation with a network of TFs (Irf4, RUNX3 and T-bet) [126]. The HMT SUV39h is responsible for H3K9me3, driving transcriptional silencing [127].…”
Section: Epigenetic Mechanisms Underlying Cd8 + T Cell Functionsmentioning
confidence: 99%
“…VIPER successfully profiled delicate differences between subpopulations and between MPR and Non (Figures 3B-D). BATF2, upregulated in CD8.c05 cells in the MPR (Figure 3B), was shown to be essential for epigenetic reorganization of chromatin during CD8 + Teff differentiation in cooperation with RUNX3 and IRF4 (86).…”
Section: Multimodal Analysis Revealing Stat5 Regulation Of Adgre5mentioning
confidence: 98%